Virulence factors of the oral spirochete Treponema denticola - Dashper, S G; Seers, C A; Tan, K H; Reynolds, E C (Journal of dental research, 2011)
There is compelling evidence that treponemes are involved in the etiology of several chronic diseases, including chronic periodontitis as well as other forms of periodontal disease. There are interesting parallels with other chronic diseases caused by treponemes that may indicate similar virulence characteristics. Chronic periodontitis is a polymicrobial disease, and recent animal studies indicate that co-infection of Treponema denticola with other periodontal pathogens can enhance alveolar bone resorption. The bacterium has a suite of molecular determinants that could enable it to cause tissue damage and subvert the host immune response. In addition to this, it has several non-classic virulence determinants that enable it to interact with other pathogenic bacteria and the host in ways that are likely to promote disease progression. Recent advances, especially in molecular-based methodologies, have greatly improved our knowledge of this bacterium and its role in disease.